Tourism Communication Strategy for Rumah Betawi Rawasapi in Conserving Local Wisdom - Yudhistira Ardi Poetra; Fina Zahra (LONTAR: Jurnal Ilmu Komunikasi, 2022)
One type of tourism that is interesting to note is cultural tourism with the concept of local wisdom. In Jatimulya, Bekasi Regency, West Java, there is a tourist attraction called Rumah Betawi Rawasapi which emphasizes the nuances of their local culture, namely the Betawi Tribe. Therefore, Rumah Betawi Rawasapi has a communication strategy to realize cultural tourism as well as being a place for preserving local wisdom. The purpose of this research is to explain and analyze the communication strategies contained in the Rumah Betawi Rawasapi in the preservation of local wisdom. This research uses a qualitative approach as a method or way to obtain research objectives. Meanwhile, the research subject is the administrator of the Rumah Betawi Rawasapi tourist attraction. The location of this research is at the Rumah Betawi Rawasapi tourist attraction which is located at Jalan Al Huda Rawasapi RT003, RW009, Jatimulya Village, South Tambun District, Bekasi Regency, West Java. The results show that there are five communication strategies at Rumah Betawi Rawasapi in preserving local wisdom as an object of cultural tourism, namely redundancy, canalizing, informative, persuasive, and educative.